Development and validation of short-amplicon length PCR assay for macaques meat detection under complex matrices - Ali, Md Eaqub; Abdul Rashid, Nur Raifana; Abd Hamid, Sharifah Bee; Hossain, Shouquat M.Azad; ..,, Asing; Hossain, Md Amzad Motalib; Sarker, Md. Zaidul Islam (Taylor and Francis Ltd., 2017)
The macaque (Macaca fascicularis) monkeys are the third largest primate population in tropical forests. Being the potential carrier of Simian Immunodeficiency and Ebola and Corona viruses, as well as being a religiously-protected and wildlife-protected species could not save the macaques from being over-hunted and consumed. Despite having needs, methods to detect monkey species in foods are rarely documented. To fill this gap, this article describes a monkey-specific polymerase chain reaction assay targeting a short-site (120 bp) of mitochondrial d-loop gene because the short-length targets are thermodynamically more stable than the longer ones under degrading states. Specificity was tested against 17 terrestrial and aquatic meat and fish species and no cross-species amplification was detected under raw, processed, and admixed states. The sensitivity of the assay was 0.0001 ng DNA under pure states and 0.1% monkey meats in binary meat mixtures. Finally, the assay was validated by digesting the polymerase chain reaction products with AluI and CViKI-1 and distinctive restriction fingerprints for macaque species were demonstrated. © 2017 Taylor & Francis Group, LLC.